2017
DOI: 10.2337/dc16-2750
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Microvascular-Linked Improvements in Glycemic Control From Resistance Training in Individuals With Type 2 Diabetes

Abstract: RT improves OGC-stimulated muscle MBF and glycemic control concomitantly, suggesting that MBF plays a role in improved glycemic control from RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 41 publications
(35 reference statements)
2
67
0
Order By: Relevance
“…Importantly, this enhanced skeletal muscle microvascular response was tightly linked to improvements in overall glycemic control including reductions in fasting blood glucose and HbA1c levels, and improvements in glucose tolerance following an OGC. Although body composition was also affected by RT, vascular and metabolic changes were not related with changes in body composition (27). This novel finding positions the microvasculature in skeletal muscle as an important regulator of overall glucose homeostasis.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Importantly, this enhanced skeletal muscle microvascular response was tightly linked to improvements in overall glycemic control including reductions in fasting blood glucose and HbA1c levels, and improvements in glucose tolerance following an OGC. Although body composition was also affected by RT, vascular and metabolic changes were not related with changes in body composition (27). This novel finding positions the microvasculature in skeletal muscle as an important regulator of overall glucose homeostasis.…”
Section: Introductionmentioning
confidence: 69%
“…Skeletal muscle is an important site for glucose disposal in response to insulin (32), and an increased microvascular blood flow (MBF) improves delivery of glucose and hormones (such as insulin) to the myocyte to improve glucose disposal (19). We have recently demonstrated that 6 wk of RT markedly enhances skeletal muscle MBF in T2D subjects in response to an oral glucose challenge (OGC) (27). Importantly, this enhanced skeletal muscle microvascular response was tightly linked to improvements in overall glycemic control including reductions in fasting blood glucose and HbA1c levels, and improvements in glucose tolerance following an OGC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that RT increased glycemic control in part by enhancing microvascular blood flow and substrate delivery to myocytes [63].…”
Section: Metabolic Control: Glycemic Control and Insulin Sensitivitymentioning
confidence: 99%
“…3 In their letter, Kotani and Gugliucci searched and compiled data from interventional studies in which the effects of physical exercise on AGEs and soluble AGEs receptors (sRAGE) were evaluated. [4][5][6][7][8][9][10] Based on those studies, the authors concluded that the practice of physical exercise could reduce serum AGEs and, seemingly contradictory, it also reduces sRAGE concentrations. 1 However, we would advert caution before drawing these conclusions.…”
Section: Dear Editormentioning
confidence: 99%